Mathematics Learning Experience: Students' Perspectives on Teachers' Teaching Approaches in the Classroom - Umam, Khoerul (Education and Talent Development Center Indonesia (ETDC Indonesia), 2025)
This study explores students’ perspectives on the mathematics learning process in the classroom, highlighting the importance of effective teaching methods. The purpose of this study is to understand students’ preferences and needs regarding the teaching styles of mathematics teachers that can improve their interest and understanding. Using a qualitative approach with a descriptive phenomenological design, data were collected through semi-structured interviews with high school students. Thematic analysis identified three main themes constructed from interview transcripts. The results showed that students desired a more student-centred mathematics learning process with a focus on practical experience and personal support. This study concluded that students desired a more intense and actual integration of the mathematics learning process with technology. Constructive feedback from teachers to students is essential for identifying errors and correcting students’ work. A teacher’s enjoyable learning style will leave a positive impression of mathematics for them in the future.